Believe in You student empowerment program: A pilot study - Erin E. Centeio; Jeanne M. Barcelona; Kevin Mercier; Aaron Hart; John T. Foley (Frontiers Media S.A., 2023)
IntroductionThe social and emotional health of youth is important, especially after students experience the COVID-19 pandemic. The purpose of this study was to understand the influence that the Believe In You Student Empowerment Program had on students social emotional learning (SEL) behaviors over a 10 week period during the COVID-19 pandemic.Materials and methodsA part of this quantitative study, one school in each the intervention and the control group (delayed intervention; 2 schools total) participated in the study. Students enrolled in physical education within each school participated (n = 166; Intervention = 88). Students in each group took a survey at week 1 (baseline measure), week 5, and week 10. Students who were in the intervention group started the program after week 1, while the delayed intervention group began the program in week 5.ResultsA series of ANCOVA's examined the difference of social emotional learning knowledge and social emotional learning scales between the treatment and control groups. Self-awareness (F = 13.91, p < .01), self-management (F = 6.14, p < .01) & relationship skills (F = 5.50, p < .05) saw significant differences over time compared to the control group. The second series of analyses looked only at the intervention group and analyzed to determine significant differences in mean scores of SEL variables between weeks one and ten. Emotional regulation saw significant differences (t = 2.5, p < .01). The final set of analyses conducted were with the delayed intervention group and examined the difference in mean SEL scores over the three time periods. Again, emotional regulation saw significance with an interaction of time and gender (F = 4.162, p < .01).Discussion and ConclusionIn a short period of time, Believe in You Student Empowerment Program has shown the potential to have a positive influence on students social emotional learning behaviors, even during the COVID-19 pandemic. More research should be conducted over a longer period of time, in-person, and with an experimental design to better understand the effects of the Varsity Brands Believe in You Student Empowerment Program and its implications with student social emotional learning behaviors.